Intervention Programme among Resettled Communities in Taraba State: Stakeholders’ Structure and Power Dynamics - Awudu, Angyu Daniel; Sha, Pam Dung; Adakai, Filicus Amayah (Kashere Journal of Politics and International Relations, 2025)
The study deployed a qualitative approach (Key Informant Interview) to elicit information from its sample subjects. The objective is to assess stakeholders’ structure and power dynamics in the NEFSLESP intervention programme implemented under the auspices of Fadama-III-AF-II in Taraba State. A purposive sampling was used to select 15 key informants. The stakeholders ' structure and interests are critical to the effectiveness of every development intervention. Who then were the stakeholders in the NEFSLESP intervention programme and what were their power distribution and interests? The findings reveal that Fadama officers (National, State and Local levels), community leaders, politicians, development agents, and service providers constitute the major stakeholder structure of the NEFSLESP intervention programme. The World Bank, the Nigerian Government, and the community leaders influenced the policy agenda of the intervention. The study further found that the programme's demand-driven nature meant the beneficiaries' ideas and needs dominated the intervention design. The key development values of the intervention include participatory governance, inclusivity, and demand-driven assistance. The power dynamics analysis also shows that the stakeholders identified exercise authority and influence based on their roles and interests. This study, therefore, contributes to political economy discourse about enhancing stakeholders' structures and power dynamics as a leads up to improving the effectiveness of intervention programmes. Thus, it recommends that the Government and civil society organisations should build systems that formally institutionalise the demand-driven nature of intervention programmes, thereby reducing elite capture of interventions.